If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -7) + 4(x + 4) = 0 Reorder the terms: 3(-7 + x) + 4(x + 4) = 0 (-7 * 3 + x * 3) + 4(x + 4) = 0 (-21 + 3x) + 4(x + 4) = 0 Reorder the terms: -21 + 3x + 4(4 + x) = 0 -21 + 3x + (4 * 4 + x * 4) = 0 -21 + 3x + (16 + 4x) = 0 Reorder the terms: -21 + 16 + 3x + 4x = 0 Combine like terms: -21 + 16 = -5 -5 + 3x + 4x = 0 Combine like terms: 3x + 4x = 7x -5 + 7x = 0 Solving -5 + 7x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 7x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 7x = 0 + 5 7x = 0 + 5 Combine like terms: 0 + 5 = 5 7x = 5 Divide each side by '7'. x = 0.7142857143 Simplifying x = 0.7142857143
| -6y=24 | | -2(3-x)=30 | | .50y=1.5 | | 15a-2(4a+5)=-6a | | 3*12=.4y | | 10=5y-3y | | 6x-3x=12 | | -6(4-2x)=12x-24 | | 4x-3x=5 | | 2.5x+1.0x=7 | | 6x+33=5x | | 5m+3=18 | | -2n+3x=7 | | .50b+6=11 | | 8-x=12-2x | | b=9b-24 | | 9y^2-33y+24= | | -9+2(4g-7)=9 | | x+4=9-2x | | m+4+5=22 | | 33=x+4 | | z=1+i^12 | | 14+4=x+5x | | -160+-52x+1x^2+x^3=0 | | 5x(3x+5)=0 | | k^3-18k-7k^2=0 | | (3s+20)(s+1)=-22 | | (3s+20)(s+1)=-20 | | 4x-8=5x-2 | | 9x+3=8x+19 | | p(p+1)=6 | | 2m^2-12m=2m-24 |